Buya Hamka: Story Analysis, and Inclusivism of Tafsir Al-Azhar - Afwi Nadia; Icha Aulia (Advances in Humanities and Contemporary Studies, 2023)
This article reviews Hamka’s discourse in interpreting stories, food, and inclusiveness in Tafsir Al-Azhar. The interesting things to discuss according to the author: first, the values of character education in the story of Prophet Yusuf as, second, the values of Indonesian inclusiveness. In order to achieve this purpose, this study uses an analysis- based library research method. The results of this study show: First, in the story of the Prophet Yusuf (peace be upon him), the values of character education, monotheism, and steadfastness have been detailed in QS Yusuf verses 3 and 112, secondly, inclusiveness is contained in Qs. Al-Hujurat verse 12 about the prohibition of prejudice and verse 13 about the nature of diversity that Allah has created.